Resolusi Konflik Kebijakan Penambangan Pasir Laut Untuk Pembangunan Makassar New Port - Alfiana (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2023)
Conflict becomes a study that cannot be separated from public policy and political interaction between stakeholders. It's just that in several developing studies, conflict is sometimes ignored and only placed as a background concept in the policy process. Whereas conflict contains dynamics that lead to the orientation of the presence of a public policy. This article describes conflict resolution regarding sea sand mining policies. This mining process is carried out to meet the material needs of the Makassar New Port (MNP) construction stockpiles on the coast of Makassar City. The research method used is a qualitative research method with an instrumental case study approach. Researchers provide a better and deeper understanding of certain issues, problems and concerns. The data analyzed were obtained from secondary data studies in the form of articles, media publications, reports and regulations, as well as primary data from in-depth interviews with parties involved in sea sand mining demonstrations. The results of the study concluded that the settlement of sea sand mining policy conflicts in Makassar City predominantly used the fight, avoiding and compromise method. The sea sand mining conflict for the construction of MNP in Makassar City has subsided after the completion of the sand mining time permit. The results obtained were only from the Kodingareng Island youth movement which received distribution of CSR funds. However, the same understanding has not been built between the government and environmental activists.